Surgical management of substernal goitres at a tertiary referral centre: A retrospective cohort study of 2, 104 patients. (March 2016) - Lin, Yann-Sheng; Wu, Hsin-Yi; Lee, Chao-Wei; Hsu, Chih-Chieh; Chao, Tzu-Chieh; Yu, Ming-Chin
Abstract: Background: When to use a thoracic approach to treat substernal goitres has often been discussed in the literature. But there are few published reports describing surgical outcomes and associated complications for patients with right-sided vs. left-sided substernal goitres. Objective: This study evaluated the characteristics and clinical outcomes of patients who underwent surgical management of substernal goitres, presenting factors indicating the use of a thoracic approach and differences between right- and left-sided goitre extensions. Design: Retrospective cohort study. Setting: Tertiary referral centre. Methods: Between January 2007 and December 2012, 2104 patients underwent thyroidectomy at Chang Gung Memorial Hospital and 140 (6.7%) were diagnosed with substernal goitres. Patient medical records were retrospectively reviewed, and data were analysed to assess surgical outcomes. Results: Seven (5.0%) patients required a thoracic approach for goitre removal. Goitre malignancy was verified in 17 (12.1%) patients. The most common postoperative complication was transient hypoparathyroidism (15.0%). Permanent RLN injury occurred in 4.3% of patients and was significantly more frequent using the thoracic approach. Unilateral extension of a substernal goitre was more common than bilateral extension. Right- and left-sided extensions occurred with equal frequency. The rate of postoperative complications was similar between groups and there were no patient deaths. Conclusion: Chest radiography and thyroid sonography may provide initial radiologic evidence of goitre extension into the superior mediastinum. Computed tomography evaluation of the depth of goitre extension to the tracheal bifurcation was the strongest predictor of the need to use a thoracic approach. There were no significant differences in the clinical features and outcomes of patients with right- and left-sided substernal goitres. The right recurrent laryngeal nerve shows increased susceptibility to damage during thyroid surgery for substernal goitres. The incidence of malignant substernal goitres is similar to that of malignant cervical goitres. Highlights: The depth of the extension to the tracheal bifurcation on CT is the strongest predictor of the need for a thoracic approach. Substernal goitres with a unilateral extension are most common with equal frequency between right- and left-sided extensions. Clinical features and surgical outcomes are the same regardless of the substernal goitre location. The incidence of malignant substernal goitres is similar to that of malignant cervical goitres.